PEMETAAN TEKNOLOGI INDUSTRI KELAPA SAWIT NASIONAL DAN KEBIJAKAN PENGEMBANGANNYA - Subiyanto, Subiyanto (Badan Pengkajian dan Penerapan Teknologi, 2011)
Palm oil industry in Indonesia has been growing rapidly. But, unfortunately the growth is only effective on upstream industry with low value products, such that potential downstream value added are not explored proportionally. The government is therefore in the process of developing an appropriate policy to strengthen the national palm oil downstream industry. This paper proposes that an approriate policy for developing palm oil downstream industry could be derived from the maps of value chain and existing technology capability of the industry. The result recommends that government policy should emphasize on the supply of raw materials, infrastructure and utilities, as well as developing the missing value chain industry, especially ethoxylation and sulfonation.